2022
DOI: 10.1038/s41467-022-30617-9
|View full text |Cite
|
Sign up to set email alerts
|

Competent immune responses to SARS-CoV-2 variants in older adults following two doses of mRNA vaccination

Abstract: Aging is associated with a reduced magnitude of primary immune responses to vaccination. mRNA-based SARS-CoV-2 vaccines have shown efficacy in older adults but virus variant escape is still unclear. Here we analyze humoral and cellular immunity against an early-pandemic viral isolate and compare that to the P.1 (Gamma) and B.1.617.2 (Delta) variants in two cohorts (<50 and >55 age) of mRNA vaccine recipients. We further measure neutralizing antibody titers for B.1.617.1 (Kappa) and B.1.595, with the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Indeed, age was a factor that correlated with declined degranulation in the lung of our Inf patients, including within the T RM fraction. However, recent studies have also shown that boosting with SARS-CoV-2 mRNA vaccines elicits competent immune responses to SARS-CoV-2 and variants of concern in older adults 41 , 42 , indicating that the responses we found in the lungs of vaccinated patients may possibly provide long-term protection. Further, the Inf group consisted of patients who recovered from mild or severe disease.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Indeed, age was a factor that correlated with declined degranulation in the lung of our Inf patients, including within the T RM fraction. However, recent studies have also shown that boosting with SARS-CoV-2 mRNA vaccines elicits competent immune responses to SARS-CoV-2 and variants of concern in older adults 41 , 42 , indicating that the responses we found in the lungs of vaccinated patients may possibly provide long-term protection. Further, the Inf group consisted of patients who recovered from mild or severe disease.…”
Section: Discussionmentioning
confidence: 62%
“…Further, we detected increased levels of IFNγ + T cell responses in blood after a recent mRNA booster-dose, as well as a modest effect of boosting towards the enhancement of IFNγ + T cell responses in the lung compared to LT vaccinated individuals. Indeed, older adults not responding to vaccination have been shown to benefit from a third dose 39 , and there is an obvious benefit of boosting to provide a higher degree of antibody-mediated protection from infection in the context of a high incidence of VOC 1 , 42 . Still, if virus neutralization is unable to completely block infection, a more robust and broader T RM response established in the lung of convalescent-infected individuals may have more chances of limiting disease.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study with two age groups (vaccine receivers under 60 and over 80) compared antibody response after the 1st and 2nd dose of the vaccine. While the majority of participants in both groups produced specific IgG neutralising antibody titres, these were significantly lower in elderly participants [ 59 ]. Conversely, vaccine kinetics at later timepoints (>3 months) demonstrated comparable neutralising titres between the two groups (<50 vs. >55 years) [ 60 ].…”
Section: Causes Of Deviant Immune Response In Viral Infectionsmentioning
confidence: 99%
“…Following two doses of mRNA vaccination, evidence shows that older individuals mount a comparable humoral immune response to the adult group [45] . However, a lower neutralizing antibody response, particularly against Variant Of Concerns (VOC), and decreased production of interferon-γ and interleukin-2 induced by SARS-CoV-2 spike-specific T cells in the elderly age group, along with declining antibody titers, have been used to justify booster doses in these populations [45] , [46] , [47] . Patients with solid cancer over 65 years old are likely to develop inadequate humoral immune responses and may benefit from booster doses.…”
Section: Discussionmentioning
confidence: 99%